The Urgency Of Influence For Madrasah Head Leadership In Improving Madrasah Quality - Siti Mulyanah (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2023)
Becoming a madrasa head is certainly not an easy thing to go through. However, when we have the desire to try to know, understand and live it sincerely, then things that are considered difficult will become easy if we are willing to carry out them wholeheartedly in carrying out this noble task. Studies of the success of madrasah principals in leading school institutions show that madrasah principals carry out their duties well. The madrasa head must have an effective strategy to organize and direct his subordinates. It can be concluded that the success of the principal is the success of all. Therefore, school principals are the most important in improving the performance and quality of education. The madrasa head is an innovator as the creator of a madrasa culture and climate that is conducive and innovative for student learning. This also includes the role of the madrasa head as a manager because as a madrasa head he must be able to create a madrasa culture and climate that is conducive and innovative for student learning. Madrasah heads are required to have 5 competencies: individuality competency, managerial competency, entrepreneurial competency, supervision competency, social competency.